Artificial intelligence contributes to the creative transformation and innovative development of traditional Chinese culture - ZHANG, Junhao (International Journal of Computational and Experimental Science and Engineering, 2025)
In recent years, artificial intelligence (AI) has emerged as a transformative force in various fields, including the arts and culture. This is particularly evident in the context of traditional Chinese culture, where AI has become a powerful tool in its creative transformation and innovative development. With its advanced capabilities in data processing and generating new ideas, AI is not only helping to preserve the rich heritage of Chinese culture but is also playing a crucial role in its evolution. This study aims to delve into how AI is reshaping the traditional elements of Chinese culture, such as calligraphy, Chinese paintings and traditional artworks, and assess its impact on both conservation and modern reinterpretation. We also examine real-world applications and projects that utilize AI technologies, such as machine learning, natural language processing, and computer vision. Our findings indicate that AI's contribution to traditional Chinese culture is multifaceted. One of the key areas where AI has made a significant impact is in the preservation and restoration of cultural artifacts. AI algorithms have demonstrated remarkable proficiency in analyzing large datasets of historical texts and artworks, uncovering previously unknown patterns and facilitating the restoration of ancient texts and relics. The integration of artificial intelligence into the realm of traditional Chinese culture signifies a pivotal moment in its history. AI's role extends beyond mere preservation; it is a catalyst for innovation, fostering new forms of artistic expression and promoting a dynamic cross-cultural exchange. As AI technology continues to evolve, it is expected to further revolutionize the way we interact with and understand traditional Chinese culture, opening up new avenues for creative exploration and cultural dialogue. This study underscores the potential of AI as a tool for cultural enrichment and highlights the exciting prospects for future developments in this area.